STRATEGIC PLANNING TRENDS IN THE REGIONS (ON THE EXAMPLE OF THE ALTAI TERRITORY) - Sannikova, I. N.; Borisova, D. E.; Krayushkin, M. G. (Economics Profession Business, 2022)
The article contains the features of regional strategic planning in the context of the implementation of the national priority — people-saving. The purpose of the study is to determine the key vector of regional strategic planning, taking into account current trends and realities of the pandemic. The study is based on official data from the Federal State Statistics Service. The basis of the research methodology is a logical-epistemological toolkit with a linkage of general scientific methods of comparison and correlation analysis. It was found that the mortality rate of the population is of critical importance in achieving national strategic priorities. And, consequently, the identification of factors of an increased mortality rate is a priority analytical task in the implementation of a regional strategy of socio-economic development. The results of the studies carried out provide the initial basis for the development of municipal strategies. In order to concretize targeted management decisions, it is further necessary to determine the relationship between mortality from specific diseases and the availability of doctors in the relevant specialties, with access to the schemes of targeted training of doctors for municipalities. More ambitious further tasks — to identify factors and assess the strength of their influence on the mortality of the population; to create an integrated model using Data Mining tools, which provides support for making management decisions aimed at reducing mortality in the region.